If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + 2b = 3(b + 8) + -3 Reorder the terms: 23 + 2b = 3(8 + b) + -3 23 + 2b = (8 * 3 + b * 3) + -3 23 + 2b = (24 + 3b) + -3 Reorder the terms: 23 + 2b = 24 + -3 + 3b Combine like terms: 24 + -3 = 21 23 + 2b = 21 + 3b Solving 23 + 2b = 21 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 23 + 2b + -3b = 21 + 3b + -3b Combine like terms: 2b + -3b = -1b 23 + -1b = 21 + 3b + -3b Combine like terms: 3b + -3b = 0 23 + -1b = 21 + 0 23 + -1b = 21 Add '-23' to each side of the equation. 23 + -23 + -1b = 21 + -23 Combine like terms: 23 + -23 = 0 0 + -1b = 21 + -23 -1b = 21 + -23 Combine like terms: 21 + -23 = -2 -1b = -2 Divide each side by '-1'. b = 2 Simplifying b = 2
| 2(5x-4)=6x+12 | | -0/4+1= | | 5(5x-4)=-9x+2 | | -4y-2(4-3y)=3(y-4) | | 8(x+4)+5=101 | | 5x-2(3+x)=2(x+2) | | -6x-8+2=4x+20 | | 2(5)(3)= | | 2(x-9)+12=19 | | 2xy+7xy+5xy= | | 3(5x+2)-x=2(x-3) | | 3X=9X+3 | | -5/11+5/22= | | (-7b^2+12)+(-10b^2+4)= | | 6x+12=3x-24 | | 8x-5=-4x+19 | | -20z-0.6=30z+1.3 | | 7(100+10)= | | w-38-34=-21 | | c-6=-9 | | 17x-7=2-x | | 9x-77=2x | | 3(50+25)= | | 19y=76 | | 4.87=m+0.87 | | 3(x-6)=9(x-2) | | 6-4(1-2x)=-23+3x | | 23+x=33 | | -2y^2+3y=-14 | | 6.4x=0.64 | | p+.03p=154.5 | | x-3.4=3.6 |